TANGGAPAN AUDIENS TERHADAP PROMOSI DIGITAL DI OBJEK WISATA DANAU TAJWID DI KECAMATAN LANGGAM MELALUI MEDIA SOSIAL. - Asrokh, Matasyah; Yulia, Nur Arini (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyze audience responses to digital promotions through social media managed by the Tajwid Lake tourist attraction, based on visitor responses. It also provides an overview of the AIDA indicators used to measure audience responses to digital promotions through social media at the Tajwid Lake tourist attraction. The background of this study is based on the importance of utilizing social media as a means of tourism promotion in attracting attention, interest, and desire, ultimately leading to tourists' actions to visit the Tajwid Lake tourist attraction. The method used was descriptive quantitative, using simple random sampling, and a sample size of 100 respondents. Data collection was conducted through direct observation of social media used by the management for digital promotion, questionnaire distribution, and documentation. The data were then analyzed using descriptive statistics. The results showed that digital promotion at the Tajwid Lake tourist attraction was effective. Of the four indicators—Attention, Interest, Desire, and Action (AIDA), Attention was the indicator that received the most positive audience response. Therefore, it can be concluded that the digital promotion implemented was able to attract audiences, but further efforts are needed to encourage them to take concrete action in the form of a decision to visit. Keywords: Response, Digital Promotion, Tajwid Lake, Social Media.